Socialization of Prevention and Handling of Violence in Higher Education in Three Study Programs: Public Sector Financial Management, Public Sector Accounting, and Digital Business at the Lombok Business Academy campus. - Damayanti, Sri; Kurniawan, Panji Rizki; Pranata, Andi; Alwyah, Lila; Dirman, Dirman; Imron, Imron (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Background: Violence is now spreading in universities, and in almost every university in Indonesia. However, the issue of sexual violence is not widely covered in the media, both electronic and social media. Therefore, education on the prevention of violence in higher education is needed, because many students become victims.Purpose of Community Service: Provide education to students about the prevention of violence in higher education environments in three departments: Public Sector Financial Management, Public Sector Accounting, and Digital Business at the Lombok Business Academy. Based on Permendibudristek No. 55 of 2024, PPKPT aims to create a safe, inclusive, and violence-free campus environment through education on safe reporting and assistance for victims.Community Service Method: The method used is to provide socialization on the prevention of violence in higher education. The result of this community service activity is to provide students with an understanding of the prevention of violence in higher education environments. Community Service Results/Findings: The results of this community service are so that students gain knowledge and understanding regarding the issues of violence that are rife and efforts to prevent and handle them as a form of creating a campus culture that is safe from violence and makes students feel comfortable to grow and become superior and characterful students.